DEVELOPING ENGLISH SPEAKING SKILLS OF ENGINEERING STUDENTS THROUGH REAL-LIFE SIMULATIONS - Babayeva Gulnozaxon Latibjonovna (Bright Mind Publishing, 2025)
This paper explores the effectiveness of real-life simulations in developing English speaking skills among engineering students. It highlights the growing need for oral communication in technical fields and presents simulations as a learner-centered, interactive approach. The study outlines various simulation strategies, implementation techniques, and classroom benefits, while also addressing challenges and offering solutions. The conclusion emphasizes that simulation-based speaking practice enhances fluency, confidence, and real-world readiness for students in technical disciplines.